The history of assisted reproductive technologies: from prohibition to recognition. - Petrushko, Maryna; Piniaiev, Volodymyr; Yurchuk, Taisiia (History of science and technology, 2021)
The birth of children after infertility treatment of married couples with the help of assisted reproductive technologies has become a reality after many years of basic research on the physiology of reproductive system, development of oocyte’s in vitro fertilization methods and cultivation of embryos at pre-implantation stages. Given the widespread use of assisted reproductive technologies in modern medical practice and the great interest of society to this problem, the aim of the study was to trace the main stages and key events of assisted reproductive technologies in the world and in Ukraine, as well as to highlight the activities of outstanding scientists of domestic and world science who were at the origins of the development of this area. The paper used historical methods to study and interpret the texts of primary sources and present scientific historical events. In addition, the current trends in assisted reproductive technologies are covered based on the results of our own, more than 30 years of experience in the field of reproductive biology and medicine, and the achievements of world scientists. As a result of the work, it has been shown that despite certain ethical and social biases, the discovery of individual predecessor scientists became the basis for the efforts of Robert Edwards and Patrick Steptoe to ensure birth of the world's first child, whose conception occurred outside the mother's body. There are also historical facts and unique photos from our own archive, which confirm the fact of the first successful oocyte in vitro fertilization and the birth of a child after the use of assisted reproductive technologies in Ukraine. Over the last 20 years, assisted reproductive technologies have continued to grow, addressing many other issues of reproductive potential preservation and infertility treatment. State of the art methods of assisted reproductive technologies include the development of cryopreservation method of gametes and embryos by vitrification, genetic screening of embryos in order to prevent the hereditary diseases transmission and embryo transfer with chromosomal abnormalities, the birth of a child “from three parents” in severe cases of mutations in the mitochondrial genome, etc
Keywords: reproductive cells; embryos; in vitro fertilization; first “test tube” child; demography; infertility treatment